2011
DOI: 10.2174/1874325001105010389
|View full text |Cite
|
Sign up to set email alerts
|

Supracondylar Osteotomies of Posttraumatic Distal Humeral Deformities in Young Adults - Technique and Results

Abstract: Background: Cubitus varus deformity is the most common late complication after distal humeral fractures in children. Typical symptoms are increasing instability especially the posterolateral rotatory instability (POLRI), lateral elbow pain and cosmetic problems. Different ways of correction have been described but a gold standard has not yet been established.Methods: In this study the clinical outcome 6,5 months after supracondylar closed wedge osteotomy stabilized wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Buß FR et all. [3] had the same results in his cases report, recommending the using of closed wedge osteotomy and plate.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…Buß FR et all. [3] had the same results in his cases report, recommending the using of closed wedge osteotomy and plate.…”
Section: Discussionmentioning
confidence: 59%
“…Different ways of osteotomies and different methods of fixation with k-wires, external fixation, screws or plates have been published. [3,6,19,20] Preoperative planning is important so that the surgeon can consider the pitfalls ahead of time. [18] The lateral approach triceps-sparing, used in this study, is easier and safer compared to posterior approach in particular considering the nerve palsies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, protrusion of the lateral condyle or S-shaped deformity of the elbow may develop postoperatively [ 20 , 21 ]. Buß et al [ 22 ] have recommended supracondylar humerus closed wedge osteotomy with a locking plate fixation in adults. Moon et al [ 21 ] have suggested medialization of the distal fragment for an effective treatment of cubitus varus deformity with minimized risk of ‘lazy S’ deformity.…”
Section: Discussionmentioning
confidence: 99%